Second law assessment of nanofluid flow in a channel fitted with conical ribs for utilization in solar thermal applications: Effect of nanoparticle shape. (April 2020) - Bahiraei, Mehdi; Monavari, Ali; Moayedi, Hossein
Highlights: Second law characteristics of the nanofluid in a rectangular channel enhanced with the conical ribs. The effects of different arrangements of the ribs and various shapes of the nanoparticles. By the increase in rib height and the reduction in the rib pitch, the total entropy generation diminishes. Using the platelet-shaped nanoparticles besides greater rib heights and lower rib pitches are optimal. The Bejan number demonstrates the great values in all the cases under evaluation. Abstract: This research tries to assess the second law characteristics of the water–boehmite alumina nanofluids in a rectangular channel enhanced with the conical ribs. The effects of different arrangements of the ribs and various shapes of the nanoparticles are evaluated. Shear Stress Transport (SST) k-ω model is implemented to perform the simulations. Based on the observations, the highest and lowest temperature gradients occur at the dead zones and the reattachment regions, respectively. For all the nanoparticle shapes, by the increase in the rib height and the reduction in the rib pitch, the entropy generated by the heat transfer diminishes while the entropy generated by the friction intensifies. Because of the dominance of the thermal entropy generation compared to the fractional one, the total irreversibility decreases by rising the rib height and reducing the rib pitch. The Oblate spheroid (Os)-shaped nanoparticles cause the highest thermal entropy generation followed by the brick-, blade-, cylinder-, and platelet-shaped nanoparticles, respectively. Moreover, the maximum frictional entropy generation belongs to the nanofluid having the platelet-shaped nanoparticles followed by respectively the cylinder-, blade-, brick-, and Os-shaped nanoparticles. The results also reveal that using the platelet-shaped nanoparticles besides greater rib heights and lower rib pitches are optimal based on the second law of thermodynamics causing the smaller total irreversibility. Furthermore, the Bejan number demonstrates the great values in all the cases under study.